Ferritin Levels and Type 2 Diabetes Mellitus: A Contemporary Review - Abdulameer, Ali Nahedh; Alamer, Noor; Kadhim, Doaa Amer (Medical Science Journal for Advance Research, 2026)
Compared to other diseases, the burden of type 2 (diabetes mellitus) is increasing globally. Currently, there are over 500 million adults diagnosed with T2DM worldwide. The effect of T2DM on the economy and health care system will cost nearly 10% of the total global healthcare expenditure. Although hyperglycemia remains a classic symptom of T2DM, it is also now recognized as a truly systemic disease, as T2DM exhibits chronic low-grade inflammation, oxidative stress and metabolic dysregulation. There has been a great deal of attention focused on ferritin, which is considered the primary iron-storage protein, as a potential biomarker of the relationship between iron metabolism, glycemic control and inflammation. serum ferritin levels that are elevated above normal values have been shown to consistently predict high rates of poor glycemic control, insulin resistance, and cardiovascular risk. Furthermore, elevated serum ferritin levels have also been shown to correlate positively with inflammatory markers such as C-reactive protein (CRP) and interleukin-6 (IL-6), suggesting that elevated ferritin may play a more general role in metabolic syndrome. The review explores new evidence (2023–2025) regarding populations from Africa, Asia, Europe and North America while assessing the methodological strength and weaknesses of the evidence. There is consistency in finding an association between ferritin concentrations, HbA1c, fasting blood glucose and metabolic complications; however, there are conflicting reports concerning whether ferritin is a causal mediator or an acute-phase reactant. Evidence from therapeutic studies showed that there was a decrease in ferritin in those receiving both a pharmacological and a lifestyle intervention, providing further support to the potential of ferritin as a tool to monitor treatment effects. The bulk of studies on this issue are cross-sectional, which does not allow you to determine causality (some are measuring ferritin levels using different assay techniques), and the large variety of baseline ferritin assays and subject populations are also complications for standardization. Future research should be longitudinal in nature and take into account ferritin measurements in combination with other inflammatory markers (CRP, IL-6, and adiponectin), and additionally use predictive models to determine how ferritin contributes to the stratification of risk as well as to the individualized treatment of patients with T2DM.